Students’ perception of their learning experience from their workload and competence development: a study about the implementation of the Bachelor’s degree in Translation and Interpretation of the Pompeu Fabra University - Roca-Cuberes, Carles (Revista Complutense de Educación, 2013)
This pilot study analyzes the implementation of the first year of the new Bachelor’s Degree in Translation and Interpretion of the Pompeu Fabra University. It examines, through a survey and focus groups, two parameters: the student’s workload, and the coherence between competences and their implementation and assessment. The results for the first parameter show that the workload is lower than the desirable 25 hours per ECTS credit. For the second parameter the results show that competence attainment is acceptable and sufficient. In general, the first year of the Bachelor’s Degree in Translation and Interpretation can be rated – from both the empirical results and a pedagogical perspective – as satisfactory. However, some issues must be addressed. For this purpose, a number of proposals for improvement are put forward. The need for studies like the present one, with a focus on students’ perception of their educational experience, is also identified.